2018
DOI: 10.1016/j.jval.2018.04.1545
|View full text |Cite
|
Sign up to set email alerts
|

Is There A Consensus Regarding Clinically Relevant Non-Inferiority Margins Used For Key Oncology Endpoints In Non-Inferiority Oncology Trials?

Abstract: Objectives: Bootstrapping is often used to assess uncertainty in outcomes of randomized controlled trials (RCTs) due to sampling variation and limited sample sizes. Although guidance is available on two-stage bootstrapping for cluster-RCTs, specific guidance is lacking on sampling clusters within bootstrap samples to address the uncertainty in variation across clusters. This study assesses the impact of using different selection approaches to sample clusters in two-stage bootstrapping in a case study on procal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The efficacy endpoints included in the PSM analysis were overall sur- [15]. Results that did not achieve significance and did not qualify per the noninferiority criteria were treated as inconclusive.…”
Section: Analysis Variables and Statistical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy endpoints included in the PSM analysis were overall sur- [15]. Results that did not achieve significance and did not qualify per the noninferiority criteria were treated as inconclusive.…”
Section: Analysis Variables and Statistical Methodologymentioning
confidence: 99%
“…Response rates and AEs were analyzed based on an odds ratio calculated using a two‐sided 95% CI by fitting a logistic regression model. Results that did not achieve statistical significance (5%) were interpreted with the use of noninferiority margins [ 15 , 16 ]. A targeted literature review identified noninferiority margins for response, safety, PFS, and OS as follows: 13% (rate difference), 13% (rate difference), 1.333 (HR), and 1.298 (HR), respectively [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute rate difference and odds ratios (ORs), calculated with two‐sided 95% CIs, were used to determine treatment response and safety outcomes; P ‐values for ORs were determined using the two‐sided Fisher's exact test. Based on recent oncology studies, results that did not achieve statistical significance (5%) were interpreted with the use of noninferiority margins [ 11 , 12 ]. Noninferiority margins for response, safety, PFS, and OS were identified as 13% (rate difference), 13% (rate difference), 1.333 (HR), and 1.298 (HR), respectively [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on recent oncology studies, results that did not achieve statistical significance (5%) were interpreted with the use of noninferiority margins [ 11 , 12 ]. Noninferiority margins for response, safety, PFS, and OS were identified as 13% (rate difference), 13% (rate difference), 1.333 (HR), and 1.298 (HR), respectively [ 11 ].…”
Section: Methodsmentioning
confidence: 99%